Astaxanthin intake attenuates muscle atrophy caused by immobilization in rats. Issue 15 (1st August 2016) - Shibaguchi, Tsubasa; Yamaguchi, Yusuke; Miyaji, Nobuyuki; Yoshihara, Toshinori; Naito, Hisashi; Goto, Katsumasa; Ohmori, Daijiro; Yoshioka, Toshitada; Sugiura, Takao
Abstract: Astaxanthin is a carotenoid pigment and has been shown to be an effective inhibitor of oxidative damage. We tested the hypothesis that astaxanthin intake would attenuate immobilization‐induced muscle atrophy in rats. Male Wistar rats (14‐week old) were fed for 24 days with either astaxanthin or placebo diet. After 14 days of each experimental diet intake, the hindlimb muscles of one leg were immobilized in plantar flexion position using a plaster cast. Following 10 days of immobilization, both the atrophic and the contralateral plantaris muscles were removed and analyzed to determine the level of muscle atrophy along with measurement of the protein levels of CuZn‐superoxide dismutase (CuZn‐SOD) and selected proteases. Compared with placebo diet animals, the degree of muscle atrophy in response to immobilization was significantly reduced in astaxanthin diet animals. Further, astaxanthin supplementation significantly prevented the immobilization‐induced increase in the expression of CuZn‐SOD, cathepsin L, calpain, and ubiquitin in the atrophied muscle. These results support the postulate that dietary astaxanthin intake attenuates the rate of disuse muscle atrophy by inhibiting oxidative stress and proteolysis via three major proteolytic pathways. Abstract : In this study, we demonstrated that dietary astaxanthin intake attenuated the rate of immobilization‐induced soleus muscle atrophy in rats by inhibiting oxidative stress and proteolysis via three major proteolytic pathways. These findings indicate that astaxanthin supplementation could be an effective countermeasure against disuse muscle atrophy.